Genetic Diversity and Demographic History of the Terrestrial Hermit Crabs Birgus Latro and Coenobita Brevimanus in the North-Western Pacific Region. Issue 6 (1st November 2015) - Hamasaki, Katsuyuki; Iizuka, Chikako; Ojima, Asuka; Sugizaki, Mio; Sugimoto, Ayaka; Dan, Shigeki; Kitada, Shuichi
Abstract: We evaluated the genetic diversity and demographic history of the terrestrial hermit crabs Birgus latro and Coenobita brevimanus using mtDNA COI sequence data (573 bp). Tissue samples from 163 individuals of B. latro and 63 individuals of C. brevimanus were collected at 11 and four localities in the North-Western Pacific Region, respectively. Haplotype diversity was high and similar in B. latro (0.8809) and C. brevimanus (0.9222). Nucleotide diversity was higher in C. brevimanus (0.01088) than in B. latro (0.00404). No genealogical structure was observed in haplotypes of B. latro whereas four haplotype clades were found in C. brevimanus . Weak but significant genetic population structure with the isolation by distance was detected in B. latro, but no genetic population structure was observed in C. brevimanus, likely because of the small number of sampling localities for the latter. Demographic history analyses suggested that B. latro and C. brevimanus had different histories of population expansion. Birgus latro experienced population expansion once during the glacial period when sea levels were relatively lower in the late Pleistocene. Conversely, it was inferred that haplotype clades of C. brevimanus diverged during or near the interglacial period when sea levels were relatively higher, and their population expansion and remixing occurred through the glacial periods in the late Pleistocene.